LESS CONSUMING WATER MOP - ARCHANA, B.; SATHISH, K.; RAM, B.SURESH; DEEPTHI, M.; MAHESH, N.UMA (The journal of contemporary issues in business and government, 2022)
In this project we are introducing “LESS CONSUMING WATER MOP” is a mop which is used to reduce water wastage and making cleaning work easier .The mop itself release water according to our control by using tap system ,which prevents the wastage of water. Mop handle should be non rusted and long lasting and this can be maintained by using C p v c (CHLORINATED POLYVINYL CHLORIDE)which is strong and durable. Reduces hard work of carrying bucket of water with us.We can connect mop to the external water tap by water passage pipe ,if there is large area of floor cleaning and carrying of water bucket is not required .It can be use at home ,hospitals, working areas etc.